Raman difference spectroscopy: a non-invasive method for identification of oral squamous cell carcinoma: publisher's note - Knipfer, Christian; Motz, Johanna; Adler, Werner; Brunner, Kathrin; Gebrekidan, Medhanie; Hankel, Robert; Agaimy, Abbas; Will, Stefan; Bräuer, Andreas; Neukam, Friedrich Wilhelm; Stelzle, Florian (Biomedical Optics Express, 2015)
The author list appeared incorrectly in [Biomed. Opt. Express 5(9), 3252-3265 (2014)]. The author names were corrected online as of January 17, 2015: https://www.osapublishing.org/boe/abstract.cfm?uri=boe-5-9-3252.[This corrects the article on p. 3252 in vol. 5, PMID: 25401036.].

Raman Differenz-Spektroskopie für die nicht-invasive optische Biopsie des oralen Plattenepithelkarzinomes - Knipfer, Christian; Motz, Johanna; Adler, Werner; Brunner, Kristin; Gebrekidan, Medhanie; Hankel, Robert; Agaimy, Abbas; Bräuer, Andreas; Neukam, Friedrich Wilhelm; Stelzle, Florian; Will, Stefan (66. Kongress der Deutschen Gesellschaft für Mund-, Kiefer- und Gesichtschirurgie, 2016)